Effect of the health and wellness Kneipp concept on health promotion and reduction of sick days for kindergarten children: a cluster randomized controlled trial protocol - Gerganova, Marinela; Schepanski, Steven; Bogdanski, Martin; Kandil, Farid I.; Tekath, Angela; Jeitler, Michael; Stritter, Wiebke; Blakeslee, Sarah B.; Seifert, Georg (Frontiers in Medicine, 2024)
Background: The holistic health and wellness Kneipp concept, has a long tradition in Europe with demonstrated health benefits. Based on the five elements of the Kneipp concept, kindergartens in and around Germany are used to certify "Kneipp Kindergartens" that practice regular Kneipp applications and activities: cold water applications, exercise, nutrition, herbs and mind-body interventions. Little is known about the potential health benefits for children, however. This study protocol describes our study design and intervention of the Kita Kneipp Study to investigate the effect of the Kneipp concept on kindergarten children aged 2-6 years.The Kita Kneipp Study, registered with the German Clinical Trial Register (DRKS-ID: DRKS00029275), is a confirmatory, mixed-method, two-armed, waitlist, clinical, cluster randomized controlled trial (RCT). Kindergartens in Berlin, Germany that would like to implement the Kneipp concept into their facility will be recruited and randomized to the intervention or control group. Changes in the number of kindergarten sick days will be the primary outcome measure. Kindergarten attendance and reason for absence including illness will be collected on a weekly basis at two time points for 6 weeks from the parents and kindergarten directors: baseline and one year after baseline. Secondary outcomes will measure cold symptoms through the Common Cold Questionnaire (CCQ) and National Cancer Institute -Common Terminology Criteria for Adverse Events (NCI-CTCAE) Scales describing gastroenterological-based symptoms Kindergarten educator sick days will be aggregately reported for the same time period. Kneipp concept activities will be recorded on a weekly basis over the one-year intervention period. To understand the experience of Kneipp concept implementation and possible changes in the kindergarten, expert interviews will be conducted with intervention kindergarten educators and focused ethnographies will be planned to observe and analyze the intervention activities. Discussion: This mixed method study design has potential to help identify if the Kneipp concept can be used for salutogenic purposes among young children and provide insights and experience of the implementation and practicing a holistic health and wellness concept in a kindergarten setting.